AB1298-HPR RHEUMA-VOR: A PROOF-OF-CONCEPT NETWORK STUDY FOR THE IMPROVEMENT OF RHEUMATOLOGICAL HEALTH CARE THROUGH COORDINATED COOPERATION. (2nd June 2020) - Dreher, M.; Schmidt, R. E.; Witte, T.; Assmann, G.; Hoeper, K.; Triantafyllias, K.; Zeidler, J.; Binder, H.; Schwarting, A.
Abstract : Background: Rheumatoid arthritis (RA), psoriasis arthritis (PsA) and spondyloarthritis (SpA) are the most common chronic inflammatory rheumatic diseases. For all three diseases, the so-called "window of opportunity" [1, 2, 4] has been identified as the decisive factor affecting the outcome. Objectives: The aim of the prospective study is to improve the early diagnosis of RA, PsA and SpA and thus positively impact the quality of care for patients with the support of coordinating centers. Methods: Primary care providers are given access to screening questionnaires to document potential early cases of RA, PsA, and SpA, based on characteristic symptoms. These are evaluated by multidisciplinary teams at the regional coordinating centers. If they fulfill the criteria for referral, patients get an appointment at a cooperating rheumatology specialist within weeks. If a rheumatic disease is diagnosed, physicians and patients receive questionnaires about sociodemographic, physilogical and psychological parameters. In order to increase the quality of referrals, a 15-minute rheumatological consultation at the ACURA Rheumatology Center was implemented for all patients from Rhineland-Palatinate whose suspected diagnosis was confirmed by the coordination centre. In course of this, the Rheuma-VOR Screening-App will also be developed and optimized. The cooperating partners and additional information are already published [5]. Results: Preliminary data (31 Dec 2019) are presented. In Rhineland-Palatinate, Saarland and Lower Saxony, 4942 suspected diagnoses of 1526 different referring physicians have now been reported. A total of 2578 patients were referred by the three coordination centres to one of the 49 participating rheumatological specialists. 1004 patients were diagnosed with one of the three diseases. About 306 patients have already taken the follow-up appointment after one year. In course of a screening consultation 736 patients have been screened to date. The patients have to wait in average about 42 days from the suspected diagnosis to the rejected or confirmed rheumatological diagnosis. Conclusion: Although the average waiting time for all three diseases is currently almost twice as long as the 23.9 days in the Rhineland-Palatinate predecessor project ADAPTHERA which just focuses on RA, the current results are very positive compared to the national average [3]. The aim is to further increase the screening quality and screening numbers, especially in the 1-year follow-up. Current data will be presented at the conference. References: [1]Boehncke WH, Menter A (2013) Burden of disease: psoriasis and psoriatic arthritis. Am J Clin Dermatol 14:377-388 [2]Claudepierre P (2014) Spondyloarthritis: a window of opportunity? Joint Bone Spine 81:197-199 [3]Lauter A, Triantafyllias K, Leiß R et al. (2019) ADAPTHERA—Statewide cross-sectoral care network for patients with early rheumatoid arthritis shows sustained remission in standard care. ZRheumatol. 78 (7): 660–669 [4]O'dell JR (2002) Treating rheumatoid arthritis early: a window of opportunity? Arthritis Rheum 46:283-285 [5]Schwarting A (2018) From ADAPTHERA to Rheuma-VOR: Concept of Coordinated Cooperation to Improve the Quality of Rheumatology Care Akt Rheumatol 43 (05): 406-409 Acknowledgments: The authors thank all partners and participants of Rheuma-VOR Disclosure of Interests: Matthias Dreher: None declared, Reinhold E. Schmidt: None declared, Torsten Witte: None declared, Gunter Assmann: None declared, Kirsten Hoeper Consultant of: AbbVie, Celgene, , Speakers bureau: Abbvie, Chugai, Novartis, Lilly, Celgene, Sandoz Hexal, Konstantinos Triantafyllias: None declared, Jan Zeidler: None declared, Harald Binder: None declared, Andreas Schwarting: None declared